Gutenberg's Europe the book and the invention of western modernity - Barbier, Frederic (Polity Press, 2017)
"Major transformations in society are always accompanied by parallel transformations in systems of social communication--what we call the media. In this book, historian Frederic Barbier provides an important new economic, political and social analysis of the first great 'media revolution' in the west: Gutenberg's invention of the printing press in the mid-fifteenth century. In great detail and with a wealth of historical evidence, Barbier charts the developments in manuscript culture in the twelfth and thirteenth centuries, and shows how the steadily increasing need for written documents initiated the processes of change which culminated with Gutenberg. The fifteenth century is presented as the 'age of start-ups', an era of flourishing investment and research into technologies that were new at the time, including the printing press."' -- Provided by publisher